Antifungal natural products. (June 2021) - Heard, Stephanie C; Wu, Guangwei; Winter, Jaclyn M
Graphical abstract: Highlights: Natural products play a crucial role in antifungal drug discovery. Natural products represent many first-in-class antifungal agents in clinical trials with new modes of action. Drug repurposing is an advantageous new pipeline for antifungal drug development. Genomics can facilitate the discovery of new chemical scaffolds with novel mechanisms of action. Abstract : Natural products are specialized small molecules produced in Nature and play pivotal roles in many cellular processes. These compounds possess exquisite chemical diversity and represent some of the most important pharmaceutical agents in human health care. With the rampant rise of fungal pathogens that are becoming resistant to nearly all clinically available antibiotics, there is an increased urgency to find new antifungal therapies with novel modes of action. To meet this need, we must be able to quickly identify new bioactive chemical scaffolds within complex natural extracts, determine their mechanisms of action, and generate appreciable yields for preclinical studies. In this review, we will highlight naturally derived antifungal agents of clinical importance as well as those with strong potential as leads in drug development.